2021
DOI: 10.3389/fimmu.2021.750969
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp5 Activates NF-κB Pathway by Upregulating SUMOylation of MAVS

Abstract: The COVID-19 is an infectious disease caused by SARS-CoV-2 infection. A large number of clinical studies found high-level expression of pro-inflammatory cytokines in patients infected with SARS-CoV-2, which fuels the rapid development of the disease. However, the specific molecular mechanism is still unclear. In this study, we found that SARS-CoV-2 Nsp5 can induce the expression of cytokines IL-1β, IL-6, TNF-α, and IL-2 in Calu-3 and THP1 cells. Further research found that Nsp5 enhances cytokine expression thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 53 publications
(57 reference statements)
1
41
0
Order By: Relevance
“…In case of activated TopNets (Figure 2C), as expected, Calu3 and Vero cells show similar upregulated pathways such as I-kappaB kinase/NF-kappaB signaling, regulation of transcription factor (TF) activity, cytokine mediated signaling pathway, and response to stimulus. These processes are well supported by previous studies (18)(19)(20). Regulation of immune signaling pathways is another process prominently observed in COVID-19, especially production of various cytokines and chemokines (21,22).…”
Section: Overview Of the Approachsupporting
confidence: 84%
“…In case of activated TopNets (Figure 2C), as expected, Calu3 and Vero cells show similar upregulated pathways such as I-kappaB kinase/NF-kappaB signaling, regulation of transcription factor (TF) activity, cytokine mediated signaling pathway, and response to stimulus. These processes are well supported by previous studies (18)(19)(20). Regulation of immune signaling pathways is another process prominently observed in COVID-19, especially production of various cytokines and chemokines (21,22).…”
Section: Overview Of the Approachsupporting
confidence: 84%
“…Studies have shown that the ACE2-Ang II axis can induce the infiltration of macrophages and secretion of certain cytokines, including IL-6, CCL2, vascular cell adhesion molecule 1 (VCAM-1), and E-selectin, to induce endothelial dysfunction, thrombin formation, and impaired fibrinolysis ( 20 , 22 24 ). In addition to the ACE2-Ang II axis, viral protein Nsp5 and spike (S) in SARS-CoV-2 can potently induce inflammatory cytokines and chemokines IL-1β, IL-6, TNF-α, IL-2, CXCL1, CXCL2, and CCL2 expressions in monocytes/macrophage through NF-κB signaling pathways ( 25 , 26 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
“…SARS-CoV-2 NSP5 can induce the expression of cytokines IL-1β, IL-6, TNF-α, and IL-2 in Calu-3 and THP1 cells. Furthermore, they showed that NSP5 could activate the NF-κB signaling pathway and enhances cytokine expression [48].…”
Section: Resultsmentioning
confidence: 99%